Molecular dynamics studies on the buffalo prion protein. Issue 4 (2nd April 2016) - Zhang, Jiapu; Wang, Feng; Chatterjee, Subhojyoti
Abstract : It was reported that buffalo is a low susceptibility species resisting to transmissible spongiform encephalopathies (TSEs) (same as rabbits, horses, and dogs). TSEs, also called prion diseases, are invariably fatal and highly infectious neurodegenerative diseases that affect a wide variety of species (except for rabbits, dogs, horses, and buffalo), manifesting as scrapie in sheep and goats; bovine spongiform encephalopathy (BSE or "mad–cow" disease) in cattle; chronic wasting disease in deer and elk; and Creutzfeldt–Jakob diseases, Gerstmann–Sträussler–Scheinker syndrome, fatal familial insomnia, and Kulu in humans etc. In molecular structures, these neurodegenerative diseases are caused by the conversion from a soluble normal cellular prion protein (PrP C ), predominantly with α-helices, into insoluble abnormally folded infectious prions (PrP Sc ), rich in β-sheets. In this article, we studied the molecular structure and structural dynamics of buffalo PrP C (BufPrP C ), in order to understand the reason why buffalo is resistant to prion diseases. We first did molecular modeling of a homology structure constructed by one mutation at residue 143 from the NMR structure of bovine and cattle PrP(124–227); immediately we found that for BufPrP C (124–227), there are five hydrogen bonds (HBs) at Asn143, but at this position, bovine/cattle do not have such HBs. Same as that of rabbits, dogs, or horses, our molecular dynamics studies also revealed there is a strong salt bridge (SB) ASP178–ARG164 (O–N) keeping the β2–α2 loop linked in buffalo. We also found there is a very strong HB SER170–TYR218 linking this loop with the C-terminal end of α-helix H3. Other information, such as (i) there is a very strong SB HIS187–ARG156 (N–O) linking α-helices H2 and H1 (if mutation H187R is made at position 187, then the hydrophobic core of PrP C will be exposed (L.H. Zhong (2010). Exposure of hydrophobic core in human prion protein pathogenic mutant H187R. Journal of Biomolecular Structure and Dynamics 28(3), 355–361)), (ii) at D178, there is a HB Y169–D178 and a polar contact R164–D178 for BufPrP C instead of a polar contact Q168–D178 for bovine PrP C (C.J. Cheng, & V. Daggett. (2014). Molecular dynamics simulations capture the misfolding of the bovine prion protein at acidic pH. Biomolecules 4(1), 181–201), (iii) BufPrP C owns three 310 helices at 125–127, 152–156, and in the β2–α2 loop, respectively, and (iv) in the β2–α2 loop, there is a strong π–π stacking and a strong π–cation F175–Y169–R164.(N)NH2, has been discovered.